Industrial training final report : Carsem (M) Sdn. Bhd. / Danial Fakhril Ahmad Subardi - Ahmad Subardi, Danial Fakhril (Universiti Teknologi MARA, Pulau Pinang, 2024)
Carsem is a leading provider of turnkey packaging and test services to the semiconductor industry, and offers one of the largest package and test portfolios in the world. The company was founded in 1972 which is among the most experienced companies in the industry, and it is recognized as one of the largest in unit volume production. The company has over 5,000 employees and assembles in excess of 100 million units each week, more than 65 percent of this volume is fully electrically tested product. Both Carsem (M) Sdn Bhd in Malaysia and Carsem Semiconductor (Suzhou) Co., Ltd in China are active members of RBA. The company has three high-technology factories. Two factories are located in Ipoh, Malaysia, a 90-minute drive from Penang, 2 hours from Kuala Lumpur and has a daily flight to Singapore. The China factory, Carsem- Suzhou, is located in the province of Jiangsu, 50 miles west of Shanghai, started production in 2004.